English Teachers’ Challenges in Applying Open-Ended Questions in EFL Classrooms - Said, Muhammad Nur Alif; Tahir, Muh.; Asriati, Asriati (Journal of Excellence in English Language Education, 2026)
This study investigates the challenges faced by English teachers in applying open-ended questions in EFL (English as a Foreign Language) classrooms, focusing on a senior high school in Makassar, Indonesia. Open-ended questions are known to promote student engagement, critical thinking, and language fluency. However, despite their pedagogical potential, their practical use remains limited in many EFL contexts. Employing a qualitative descriptive approach, this research gathered data through in-depth interviews with four English teachers at SMA Negeri 11 Makassar. The findings reveal several persistent challenges, including limited class time, students' low confidence in speaking English, lack of teacher training, and curriculum rigidity. These obstacles hinder teachers from using open-ended questions regularly, often causing them to rely on traditional closed-ended questioning methods. The study further highlights how systemic constraints, such as time-bound learning targets and exam-oriented instruction, exacerbate the issue. These findings suggest the urgent need for institutional support, professional development programs, and curriculum flexibility to empower teachers in using open-ended questions more effectively. By exploring the lived experiences of teachers, this study contributes to the growing discourse on questioning strategies in EFL teaching and offers practical insights for improving classroom interaction in Indonesian secondary schools.